First day at school - Hughes, Monica, 1944- (Chicago : Raintree, 2004)
Describes and presents color photos of the many new experiences had by two children on their first day of school, from hanging up their coats to going to the cafeteria and recess.
Before school -- Good morning! -- In the classroom -- Reading and writing -- Math and art -- Recess -- Time for lunch -- Afternoon -- Library and music -- Time to go home.
Includes index.
Booklist.
Horn Book.
2.3.
2.3
K-3
Keywords: Early childhood education -- Juvenile literature; First day of school -- Juvenile literature; First day of school; Schools; First day of school; Schools